THE INFLUENCE OF FINANCIAL COMPENSATION, PHYSICAL WORK ENVIRONMENT, AND TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE PROVICES INDONESIA COMPANY IN THE MINISTRY OF TRADE UNIT - Hairul Hadi; Hasanudin Hasanudin (SOSIOEDUKASI, 2026)
This study aims to analyze the effect of Financial Compensation, Physical Work Environment and Transformational Leadership Style on Employee Performance, with Job Satisfaction as a mediating variable. The number of samples was 150 respondents from PT Provices Indonesia in the Ministry of Trade Unit taken using a questionnaire. Data analysis was carried out with SEM AMOS 24.0.0. The results of the study Financial Compensation is negatively insignificant or has no effect on employye job satisfaction of PT. Provices Indonesia in the Ministry of Trade unit, the physical work environment has no significant effect on employee job satisfaction has a positive and significant effect on employee performance of PT. Provices Indonesia in the Ministry of Trade unit, job sastisfaction is an important factor in improving employee.